Thoracolumbar Spine Subdural Hematoma in Infant - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
A thoracolumbar subdural hematoma (SDH) resulting from nonaccidental trauma in a 4-month-old infant is reported from Women and Children's Hospital, University of Buffalo, NY.